2014
DOI: 10.1179/1743133613y.0000000100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stirring on behaviour of double oxide film defects in A356 aluminium melt

Abstract: The effect of stirring of melt on the behaviour of double oxide film (bifilm) defects in A356 melt was investigated using a reduced pressure test (RPT) technique. The melt was poured from a height into a crucible to introduce bifilms into the melt. The melt was then either remained stagnant or mechanically stirred, and RPT samples were taken from the melt at 8 min intervals. The RPT samples were then characterised by determination of their porosity parameters and examination of the internal surfaces of the por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Some evidence for this hypothesis has been proposed by this research team. It was shown [12,13] that a crumpled oxide film defect is not detectable at the cross section of RPT samples, and that the defect becomes visible after it is expanded (at least partially) by the diffusion of H into its atmosphere. This is the reason for the initial increase in the pore number density and average pore roundness in all the experiments (see Figures 4,5,10 and 11).…”
Section: Discussionmentioning
confidence: 97%
“…Some evidence for this hypothesis has been proposed by this research team. It was shown [12,13] that a crumpled oxide film defect is not detectable at the cross section of RPT samples, and that the defect becomes visible after it is expanded (at least partially) by the diffusion of H into its atmosphere. This is the reason for the initial increase in the pore number density and average pore roundness in all the experiments (see Figures 4,5,10 and 11).…”
Section: Discussionmentioning
confidence: 97%
“…This movement assures that the overall upper medium of the crucible is contemplated by a screw type movement due to the higher linear velocity in rotation, relative to the axial linear velocity. It is known that the rate of stirring has a significant effect on the inclusion of hydrogen and oxide bifilms [26], however, the use of a translation movement is able to avoid these issues. The absence of an impeller, thus high speed rotation in turbulent paddle rotation, is able to prevent known issues such as local vortices, sloshing, and axial flow from the impeller [26][27][28].…”
Section: Ultrasonic Melt Stirring For Microparticles Dispersionmentioning
confidence: 99%
“…It is known that the rate of stirring has a significant effect on the inclusion of hydrogen and oxide bifilms [26], however, the use of a translation movement is able to avoid these issues. The absence of an impeller, thus high speed rotation in turbulent paddle rotation, is able to prevent known issues such as local vortices, sloshing, and axial flow from the impeller [26][27][28]. The m-SiCp particles used in this study were characterized considering their size distribution ( Figure 3).…”
Section: Ultrasonic Melt Stirring For Microparticles Dispersionmentioning
confidence: 99%
“…In this case the defect might be able to float out of the melt through buoyancy force. 6 On the other hand, if the two layers lie on each other (at least at some points), for example when the hydrogen content of the melt is low and the oxygen and nitrogen of the atmosphere are consumed by the reaction with the ambient melt, 7 or when the defect is in its convoluted form, then there would be a chance for the oxide layers to bond with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Amirinejhad et al 11 also suggested that if the timing of such transformation was suitable, the diffusion of hydrogen might not be able to open up the convoluted bifilms. Ahmadpour et al 6 showed that stirring the melt with a rotor could accelerate the rate of diffusion of hydrogen into the atmosphere of the bifilm defects and hence facilitate their removal from the melt by floatation.…”
Section: Introductionmentioning
confidence: 99%